2019
DOI: 10.1002/aelm.201900637
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin PEDOT:PSS/rGO Aerogel Providing Tape‐Like Self‐Healable Electrode for Sensing Space Electric Field with Electrochemical Mechanism

Abstract: A versatile composite aerogel is developed by introducing of PEDOT:PSS in reduced graphene oxide, resulting in an ultrathin aerogel film around 100 µm thick. Like a tape, the aerogel can tightly attach to smooth or rough substrate, and there forms a self‐healable and anti‐vibration energy storage electrode. With a Ti foil substrate, the electrode offers an electrochemical capacity of 190 mF cm−2 at 0.1 mA cm−2 working current density. It also exhibits 98.7% capacitance retention after 10 000 charge/discharge c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 75 publications
1
14
0
Order By: Relevance
“…Here, R s represents the series resistance, which primarily reflects the electrical contacts, wires, and sheet resistance of the electrodes [ 53 ]. The charge-transfer properties at the interface are reflected by the charge-transfer resistance ( R tr ), whereas R rec is related to the recombination of the carriers [ 54 ]. It is clear that the R s values of the two devices were similar.…”
Section: Resultsmentioning
confidence: 99%
“…Here, R s represents the series resistance, which primarily reflects the electrical contacts, wires, and sheet resistance of the electrodes [ 53 ]. The charge-transfer properties at the interface are reflected by the charge-transfer resistance ( R tr ), whereas R rec is related to the recombination of the carriers [ 54 ]. It is clear that the R s values of the two devices were similar.…”
Section: Resultsmentioning
confidence: 99%
“…The series resistance (R s ) mainly reflects electrical contacts, wires, and sheet resistance of the electrodes [43,53]. The charge-transfer resistance (R tr ) means the charge-transfer property at the interface, and R rec means the recombination of carriers [43,54]. Fitted with ZView software, it can be observed that the R s values are similar for these samples.…”
Section: Resultsmentioning
confidence: 99%
“…Scratches made by a razor blade on a porous composite aerogel (thickness of 200 µm), consisting of PEDOT:PSS and reduced graphene oxide (rGO), were healed after treatment with water vapor for 30 min. [114] This property was exploited to fabricate self-healing capacitors, which showed a retention of ≈95% after eight damaging/healing cycles. Films of a block copolymer containing PEDOT, soft segments of poly(poly(ethylene glycol) methyl ether acrylate) (PPEGMEA), and hard segments of PSS (thickness of ≈300 nm, conductivity of ≈0.05 S cm −1 ) showed water induced healing with an efficiency of ≈50%.…”
mentioning
confidence: 99%